PRIORITAS STRATEGI PENINGKATAN KOMPETENSI PETANI PADI SAWAH DI KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI PROVINSI RIAU - Sri Ayu Kurniati; Sisca Vaulina (DINAMIKA PERTANIAN, 2019)
The competence of farmers in cultivating comprises the accuracy of using production inputs, appropriate cultivation techniques, marketing of production, good administrative, and ability of using information technology. This study aims to analyze internal and external factors affecting farmers' competence and formulate strategic priorities in improving the competence of rice farmers. The research used a survey method located in Gunung Toar District, Kuantan Singingi Regency of Riau Province withnumber of sample of 50 rice farmers. The data source came from primary data and secondary data. Data were analyzed using SWOT and QSPM analysis. The results showed that the internal factors owned by farmers were the ability to use efficient marketing channels (strengths) and the use of communication tools that were still limited (weaknesses). While the external factors were the existence of government policies on food security (opportunities) and fluctuating production selling prices (threats). Through the IFE and EFE matrices, strategic positions are obtained in the ST strategy quadrant. QSPM assessment on the strategy of building cooperation with marketers as a permanent consumer is an alternative priority strategy to improve farmers' competence.